Unsuccessful subjective well-being assimilation among immigrants: The role of faltering perceptions of the host society - Martijn Hendriks; Martijn J. Burger (Tinbergen Institute, 2018)
Immigrants in developed countries typically fail to assimilate in terms of subjective well-being, meaning that their happiness and life satisfaction do not substantially increase with their length of stay or across generations, and therefore their subjective well-being remains lower than that of natives. This contrasts with migrants' own expectations and the predictions of straight-line assimilation theory, along with the general improvement of immigrants' objective living conditions with their length of stay. Using European Social Survey data, we show that the subjective well-being assimilation of first-generation immigrants in developed European countries is impaired by the gradual development of less positive perceptions of the host country's economic, political, and social conditions. These faltering societal perceptions particularly affect immigrants whose societal conditions strongly improved by migration and immigrants who arrived after childhood. Faltering societal perceptions continue to impair subjective well-being assimilation across generations. However, compared with natives, first-generation immigrants derive a subjective well-being advantage from their more positive societal perceptions. We attribute these findings to immigrants' growing aspirations and expectations that follow from their habituation to better conditions in their host country and fewer (more) comparisons to inferior (better) conditions of the people in their home (host) country. Our findings suggest that delaying or decelerating the process of immigrants' faltering societal perceptions is a promising pathway to improved subjective well-being assimilation and reduced frustration about their perceived lack of progress.
Keywords: I31; F22; 330; subjective well-being; migration; assimilation; aspirations; expectations